PENGARUH PENGGUNAAN MEDIA DREAM BOOK TERHADAP KREATIVITAS MAHASISWA - Pratiwi, Indah; Amelia, Chairunnisa; Rahma, Fanisha Alya (UIN Sumatera Utara Medan, 2023)
This research is motivated by the lack of creativity of students in making media when learning is implemented and the lack of use of media in teaching practices by students during PLP activities in elementary schools. This study aims to determine student creativity by applying Dream Book media. The research method used is quantitative research methods. The population used in this study were 4th semester students consisting of 6 classes with purposive sampling technique. The independent variable is Media Dream book while the dependent variable is student creativity. Hypothesis testing was carried out using the t test (Independent Sample T-Test), which was previously also tested for normality tests and homogeneity tests. The results of this study get a sig. 2-tailed of 0.000 where < than 0.05. So it can be concluded that there is an effect of using dream book media on the creativity of fourth semester students of class F PGSD.